2019
DOI: 10.1186/s40854-019-0141-5
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic effects of Mobile money: evidence from Uganda

Abstract: This study examined the effects of mobile money-a recent innovation in Uganda's financial-sector landscape-on aggregate economic activity and other macroeconomic variables. We first estimated the long-run mobile-money demand function using vector error correction (VEC) techniques, distinguishing between balances and transfers/ transactions. We then estimated the short-run effects of mobile money on selected macroeconomic variables using structural vector autoregressive (SVAR) methods. The results showed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Bank of Ghana (2017) documented the explosive growth of MM transactions, suggesting reduced demand for real money and increased accumulation of loanable deposits. In a similar vein, a positive relation between MM balances and private sector credit was established in Uganda (Mawejje & Lakuma, 2017). Adding weight to these findings, Nampewo et al (2016) found that MM balances led to private sector credit growth in the long run, suggesting the expansion of financial depth.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Bank of Ghana (2017) documented the explosive growth of MM transactions, suggesting reduced demand for real money and increased accumulation of loanable deposits. In a similar vein, a positive relation between MM balances and private sector credit was established in Uganda (Mawejje & Lakuma, 2017). Adding weight to these findings, Nampewo et al (2016) found that MM balances led to private sector credit growth in the long run, suggesting the expansion of financial depth.…”
Section: Resultsmentioning
confidence: 82%
“…Research at the country level, however, focuses mainly on economic growth. The introduction of MM has been found to be associated with GDP growth in Uganda (Mawejje & Lakuma, 2017) and with per capita income growth in Kenya (Beck et al, 2018; Beck, Ramrattan, Pamuk, & Uras, 2016). In his cross‐country study, Nan (2019) established the relation between MM diffusion and economic growth and further showed that the positive effect increased over time as MM spread on a massive scale.…”
Section: Resultsmentioning
confidence: 99%
“…The macroeconomic policy context also plays a critical role in the success of mobile money systems. A few studies investigate the impact of mobile money on macroeconomic policy variables (See for instance (Kipkemboi and Bahia 2019;Mawejje and Lakuma 2019)). However, there is a paucity of empirical studies on the impact of macroeconomic policy variables on mobile money.…”
Section: Macroeconomic Policy Regulation and Mobile Money Usage: An Overviewmentioning
confidence: 99%
“…Like many developing countries, the financial sector in Uganda has undergone rapid transformation over the last two and half decades (Mawejje and Lakuma 2019;Whitworth and Williamson 2010). This growth has been possible due to reforms that enabled the development of market-based institutions, particularly in the financial sector.…”
Section: An Overview Of Mobile Money In Ugandamentioning
confidence: 99%
“…For a mobile phone user who wishes to withdraw cash from the mobile wallet, the user will need to go to a mobile money agent outlet. However, due to the rapid growth of the money space, there is a lot of integration and collaboration within the ecosystem (Chauhan, 2015;Mawejje & Lakuma, 2017). As a result of cooperation and inclusion within the ecosystem, mobile phone users can now collect money from their mobile wallets through the Automated Teller Machine (ATM) in some developing markets.…”
Section: Introductionmentioning
confidence: 99%